The Urban Sustainability Index in Urban Aglomeration - Pujiati, Amin; Bowo, Prasetyo Ari; Nihayah, Dyah Maya (Universitas Negeri Semarang, 2018)
The regional autonomy positively impacts regional development in terms of competitiveness. Each area tries to have advantage from other areas. One of the parameters of city competitiveness is the concept of sustainable cities. This study aims to identify cities based on sustainable urban development indices in six urban agglomeration area of Semarang: Semarang city, Semarang regency, Kendal regency, Grobogan regency, Demak regency and Salatiga city. Methods of data collection with questionnaires, interviews and documentation. Respondents in this study were the general public, policy makers, and academics. The results showed, based on the sustainable urban development index of the Sustainable Urban Development Indonesia Forum, six districts in urban agglomeration area of Semarang are categorized as less sustainable in 2016. The regencies in the urban agglomeration areas of Semarang indicate the index result of 103,00 - 127,83. The average contribution of the urban leadership, the urban governance, the urbanization and population, the housing and settlements variables are high, while the disaster risk and the climate change, the waterfront areas, the mass transportation, the local economy and informal sector, the preservation of cultural Heritage, the natural heritage and the local Wisdom, the green Open Spaces, the emissions and energy variable are still low.